Sünnette evlenme ve evlendirmeler - Ahmedov, Reşadet (My University, 2006)
Giriş kısmında, çalışmamızın esas kısmına geçmeden önce, kıyaslama imkanına sahip olmak düşüncesiyle, umûmi olarak evlilik ve ailenin önemi, tarih boyunca farklı milletlerde veya bölgelerde rastlanan evlilikler ve bazı evlilik çeşitleri, Yahudilikte, Hıristiyanlıkta ve Cahiliye dönemindeki evliliklerle ilgili bilgilere kısaca yer verdik. Birinci bölümde, umûmî olarak İslam’da evlilik, şartları ve gâyeleri mevzûlarından bahsederken, ikinci bölümde ise her mevzûda müslümanlar için örnek olan Hz. Peygamber’in evliliklerini kaynaklardan aktardık ve ayrıca bu evliliklerdeki gâyeleri mümkün olduğu kadarıyla tespit etmeğe gayret ettik. Tespit sonucu Hz. Peygamber’in, yaptığı evliliklerinde beşerî, ailevî endişe ve himaye, insanî, içtimaî, siyasî, teşriî, tebliğî ve örneklik gibi gâyeler güttüğünü ortaya koyduk. Ayrıca, Hz. Peygamber’in evlendirdiği bazı kişileri ve evlendirme gâyelerini de bu bölümün içinde zikrettik. Üçüncü bölümde de Hz. Peygamber’i görüp, sohbetinde bulunan, dolayısıyla O’nun sünnetini en iyi anlayan Ashâbın evlenmesi ve evlendirmesini ele aldık.

This study is composed of an introduction chapter, three main chapters and a conclusion chapter. In this study, we tried to determine the marriages of the Prophet Muhammad (pbuh) and the aims of these marriages. We briefly mentioned in the introduction chapter from the importance of marriage and family, marriages in the several societies and regions throughout the history, kinds of marriages, and marriages in the Arabian Peninsula before the advent of Islam, marriages in the Christianity and Judaism in terms of making comparison between them. In the chapter one, the marriage in Islam, stipulations of the marriage and its aims are explained. In the second chapter, we tried to detect the marriages of the Prophet Muhammad (pbuh) who is the model in the all aspects of the social life for muslims. Moreover, in the same part we tried to determine aims of these marriages of the Prophet Muhammad (pbuh). This study indicates that these aims are concerned of protection of human and family; mission of modelling, notifying, legitimating. Furthermore, we also explained the marrying off the some companions by the Prophet and the purposes of these marriages . In the third chapter, we tried to detect the marriage practises of the companions of the Prophet Muhammad (pbuh). In the conclusion chapter, we briefly summarized our findings.
Keywords: Hadis; Sünnet_Evlilik